Exploring Hisbah as a supervisory mechanism for promoting Sharia compliance in modern business contexts - Dewi Mutmainnah (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2023)
Purpose — The primary goal of this study is to investigate how the supervisory role of Hisbah in Islam can effectively enhance the adherence of modern business individuals to Sharia principles.Method — This qualitative research utilizes a descriptive-analytical approach to examine the role of Hisbah in enhancing Sharia compliance among modern business practitioners. The data, obtained from various books and journals, is collected, processed, and analyzed to derive conclusions regarding the effectiveness of Hisbah in promoting adherence to Sharia principles in contemporary business settings.Result — By implementing internal Hisbah through the utilization of muraqabah and muhasabah tools, a culture of Sharia compliance can be established. Simultaneously, external Hisbah parties, such as authoritative institutions or government entities, can play a crucial role in strengthening control and supervision. This combined effort ensures that the enforcement of Sharia principles remains objective, independent, and practical. The establishment of a robust and synergistic supervisory mechanism between internal and external Hisbah, involving government authoritative institutions, can substantially contribute to achieving Sharia compliance among modern business practitioners.Contribution — This research makes a valuable contribution to the academic realm by enriching our understanding of the concept of Hisbah and its implications for Sharia compliance. It serves as an initial stimulus for future research endeavors, particularly focusing on the effectiveness of external Hisbah institutions in fulfilling their supervisory roles within modern business contexts. This research paves the way for further exploration and investigation into the topic, fostering a deeper understanding of how external Hisbah entities can effectively contribute to promoting Sharia compliance in contemporary business practices.